وجودیت، تصورِ موت اسلامی تناظر - ڈاکڑ خواجہ محمد سعید (FIKR-O NAZAR فکر ونظر, 2010)
According to existentialists, it is important that human beings be aware of death. They do not take the death negatively but hold that knowledge of death is fundamental human condition that gives meaning to living. The apprehension of death and the apprehension of life are correlated. The fear of death looms over those who are afraid to participate fully in life. They believe that people who fear death also fear life, it is as if one is saying "I fear death because I have never fully lived." According to existentialists death is of two types: Subjective death and objective death. In view of existentialists subjective death is more important because it is related to the imagination of a human being. In Islamic teachings proper conception of death is also given vital importance for a successful fulfilment of life. This article attempts to present an analysis of existentialist point of view about death in Islamic perspective.